2018
DOI: 10.1177/0022242918805411
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling Content on Social Media: Theory, Evidence, and Application

Abstract: Content platforms (e.g., newspapers, magazines) post several stories daily on their dedicated social media pages and promote some of them using targeted content advertising (TCA). Posting stories enables content platforms to grow their social media audiences and generate digital advertising revenue from the impressions channeled through social media posts’ link clicks. However, optimal scheduling of social media posts and TCA is formidable, requiring content platforms to determine what to post; when to post; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 66 publications
7
90
0
1
Order By: Relevance
“…One technique is to identify gaps in current consumer or marketer thinking and actions. For example, Kanuri, Chen, and Sridhar (2018) reviewed the services offered by major social media software platforms and interviewed social media professionals to discover a lack of a holistic social media scheduling solutions. This led to a project to fill this gap to manage the day-part timing of social media to maximize user response.…”
Section: Uncovering Research Problems In the Real World Of Marketingmentioning
confidence: 99%
“…One technique is to identify gaps in current consumer or marketer thinking and actions. For example, Kanuri, Chen, and Sridhar (2018) reviewed the services offered by major social media software platforms and interviewed social media professionals to discover a lack of a holistic social media scheduling solutions. This led to a project to fill this gap to manage the day-part timing of social media to maximize user response.…”
Section: Uncovering Research Problems In the Real World Of Marketingmentioning
confidence: 99%
“…Studies on advertising and evidence from the industry have indicated the frequency and duration of exposure to marketing communications are critical to the success of marketing campaigns [68]. Similarly, several researchers have identified posting frequency and the timing of posts (e.g., hour, day, month) as significant criteria for the success of BFPs [10,16,37,[69][70][71]. Posting too frequently may result in a situation in which there is not enough time for adequate engagement, as the post will only remain for a short time in the most visible space, the top of a BFP.…”
Section: Temporal Factorsmentioning
confidence: 99%
“…3 The exogenous component serves as a valid instrument for the endogenous variable in Equation 4. The LIV approach is widely applied in marketing (Kanuri, Chen, and Sridhar 2018; Lee et al 2015) and is well suited for survey-based settings (Gupta et al 2019). Following Ebbes et al (2005), we construct a discrete LIV with C categories (where C > 1) and obtain latent clusters on attribute dissatisfaction and satisfaction as follows:…”
Section: Modeling Approachmentioning
confidence: 99%